Negotiated Safety? Did Backpage.com Reduce Female Homicide Rates - Tjaden, Samantha L.N. (Homicide studies, 2024)
Prior research has associated Craigslist.com and Backpage.com as sources of victimization, which in part resulted in the closure of the erotic services of each respective website. However, research also claims the introduction of Craigslist was associated with a reduction in female homicide rates across 30 large cities. This research acts as a supplemental analysis to Cunningham et al. by analyzing if Backpage.com, considered to be Craigslist’s successor, has similar effects on female homicide rates. When including measures of interest in each respective website, we find that Backpage is associated with a decrease in homicide rates for women. The purpose of this study is to extend the study conducted by Cunningham et al. through supplemental analysis. To determine the effect of online clearinghouses on female homicide rates, interest measures in Backpage along with the female homicide rates from 120 single city metropolitan and micropolitan areas over 14 years (2004–2018) were analyzed using multiple regression analyses. The regression analyses show that there is a statistically significant relationship between interest in Backpage and homicide rates for women. We find that Backpage is associated with a decrease in homicide rates for women.